Understanding engineering mechanics : dynamics - Pytel, Andrew; Kiusalaas, Jaan (Australia : Cengage Learning Asia Pte Ltd, 2011)
In this edition of Dyanamics, we have made what we concsider to be a number of significant improvements based upon the feedback received from the students and faculty who have used the previous editions.
Introduction to dynamics -- Dyanmics of a particle: rectangular coordinates -- Dynamics of a particcle: curvilinear coordinates -- Work-energy and impulse-momentum principles for a particle -- Dynamics of particle systems -- Planar kinematics of rigid bodies -- Planar kinetics of rigid bodies: force-mass-acceleration method -- Planar kinetics of rigid bodies: work-energy and impulse-momentum methods -- Rigid-body dynamics in three dimensions -- Vibrations
Includes index.
Keywords: DYNAMICS